Effective Strategies for Islamic Religious Education for Children with Special Needs at SLBN 1 Padang Panjang, West Sumatera, Indonesia - Wahyuni, Sri Intan; Ramayanti, Devi; Zulfikri, Zulfikri; Sari, Azmatul Khairiah; Haruna, Dennis (Unisia, 2024)
Education for children with special needs is crucial to support their self-confidence in following an educational path according to their intellectual abilities. This research began with a problem found at SLB Negeri 1 Padang Panjang, where teachers were still using general textbooks to teach children with intellectual disabilities. In contrast, teachers should use specialized teaching guides for children with special needs. This study aims to explore Islamic Religious Education (PAI) for children with intellectual disabilities at SLB Negeri 1 Padang Panjang. The type of research used is descriptive qualitative research. This research was conducted at SLB Negeri 1 Padang Panjang, using data collection methods including observation, interviews, and documentation. The analysis technique used involves data reduction, data presentation, and conclusion. To ensure the validity of the data, perseverance and triangulation were employed. The research results show that Islamic religious education for children with intellectual disabilities at SLB Negeri 1 Padang Panjang is quite effective. Before conducting the lessons, teachers adjust the material to the students' abilities. The teaching methods the teachers use include lectures, question-and-answer, and practice exercises. The obstacles in the learning process include a lack of support from some parents. At the same time, the supporting factors are the guidance and good cooperation between most parents and the school.